Improvement of the anti-Candida activity of itraconazole in the zebrafish infection model by its coordination to silver(I) - Stevanović, Nevena Lj.; Glišić, Biljana Đ.; Vojnovic, Sandra; Wadepohl, Hubert; Andrejević, Tina P.; Đurić, Sonja Ž.; Savić, Nada D.; Nikodinovic-Runic, Jasmina; Djuran, Miloš I.; Pavic, Aleksandar (Journal of molecular structure, 2021)
In order to develop a novel antifungal agent, we synthesized and completely structurally characterized the silver(I) complex with the known antimycotic itraconazole (itraco), [Ag(itraco-N)2]NO3.H2O (Agitraco). The spectroscopic and crystallographic results revealed that, in this complex, two itraco ligands are monodentately coordinated to the Ag(I) ion via the triazole nitrogen atom forming a cationic [Ag(itraco-N)2]+ part, which is neutralized by the nitrate anion. The antifungal effect of silver(I) complex and itraconazole was evaluated against four different Candida species (C. albicans, C. glabrata, C. parapsilosis and C. krusei) by means of minimal inhibitory concentrations (MICs). Agitraco complex shows enhanced antifungal activity than itraco, being 2.3- and 4.5-fold more active against C. albicans and C. glabrata, respectively. The complex was also more efficient in inhibiting yeast to hyphae transition process in C. albicans, which is an important step in its pathogenesis. Part of the improved activity of Agitraco could be attributed to the greater induction of reactive oxygen species in Candida spp. with respect to itraco. The toxicity evaluation in the zebrafish model (Danio rerio) suggests that the Agitraco complex has better therapeutic profile and improved antifungal efficacy with respect to the parent drug, which were also proven in vivo using the zebrafish model of lethal disseminated candidiasis. Interaction of Agitraco with bovine serum albumin (BSA) was investigated with the aim to assess its binding affinity toward this biomolecule.